Interpretation and Identification of Unexploded Aircraft Ammunition Sites from Reconnaissance Flight Images - BUDAYOVÁ, Maria; SRNOVÁ, Karla; POSPÍŠIL, Jiří; ŠAFÁŘ, Václav (GeoScience Engineering, 2022)
This article describes the optimal work sequence for the interpretation and identification of unexploded aircraft ammunition sites from reconnaissance flight images of the area bombed during World War II. The described activities are based on a number of previous actions that were carried out within the framework of the MVČR security research project entitled "The search for unexploded aircraft ammunition from World War II". Two sites in the Czech Republic were selected for the project solution, which are among the most affected ones by the World War II bombing. With regard to the current knowledge and experience of the research team, a procedure of activities was suggested in order to secure the optimal quality of the results of interpretation and identification of the sites where unexploded aircraft ammunition can be found. The results may be affected by the frequency and quality of reconnaissance flight images and the information on the used aircraft ammunition. The quality of the results also depends on the quality of previous work in the creation of an orthophoto, personal experience and knowledge of the people working on the interpretation and identification of the images. Keywords: Bombing; Interpretation and identification procedure; Orthophoto image; Stereoscopic evaluation; Unexploded aircraft ammunition.